2009
DOI: 10.1111/j.1749-4486.2009.01975.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the SNOT 22 score in adults with no sinonasal disease

Abstract: Due to the scewed nature of the data, the median score (7) is taken as the normal SNOT 22 score. We recommend that in an clincial situation a SNOT 22 score of 7 be used a a guide for "normal", and that care should be taken when suggesting treatment on patients with a score below this level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
65
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 4 publications
(5 reference statements)
13
65
1
1
Order By: Relevance
“…None of the groups (except for the group that started with a mean SNOT‐22 score below that of the normal population) achieved postoperative scores below the normal mean of 9.2 . These persistent symptoms are likely to explain why, although achieving improved absolute changes in SNOT‐22 scores, those with higher preoperative scores are no more likely to rate the results of surgery as excellent or very good as those with lower scores.…”
Section: Discussionmentioning
confidence: 94%
“…None of the groups (except for the group that started with a mean SNOT‐22 score below that of the normal population) achieved postoperative scores below the normal mean of 9.2 . These persistent symptoms are likely to explain why, although achieving improved absolute changes in SNOT‐22 scores, those with higher preoperative scores are no more likely to rate the results of surgery as excellent or very good as those with lower scores.…”
Section: Discussionmentioning
confidence: 94%
“…The most widely accepted and best validated patient self-report symptom evaluation tool for use in CRS is the SNOT-22, whose 22 items incorporate both nasal and non-nasal symptoms (Hopkins,5,6 Within SNOT-22, self-reported symptom severity is graded from 0 to 5, with five being a severe problem. Patient reported outcome measures (PROMs) are a means of collecting information on the effectiveness of care delivered to patients, as perceived by the patients themselves, and are increasingly important in clinical practice and in research 2-4 on a background of increasing costs of healthcare across the world.…”
Section: Resultsmentioning
confidence: 99%
“…These near perfect CRSsNP patients had a mean SNOT-22 score of 21.6, which was 4 to 5 points worse than non-CRS controls and CRSwNP patients with near perfect endoscopy (Table 7). Previous studies have reported normative data for the SNOT-22 in non-CRS patients with a mean as low as 7 16 , however these studies typically examined medical students or other populations that were not matched for age, gender, co-morbidities and environmental exposures 171820 . When we compared our CRS cohort to a matched non-CRS cohort, we found that a “normal” SNOT-22 is approximately 16, thus this should realistically be the goal for our CRS patients, rather than a “perfect” score of 0.…”
Section: Discussionmentioning
confidence: 99%